1996
DOI: 10.1146/annurev.micro.50.1.707
|View full text |Cite
|
Sign up to set email alerts
|

Will the Real Agent of Cat-Scratch Disease Please Stand Up?

Abstract: Cat-scratch disease has been recognized since 1889 in association with the oculoglandular syndrome of Parinaud. The epidemiologic association with cats was first made in 1931 and further substantiated throughout the years, refining the interaction predominantly to kittens. Putative infectious agents have included numerous species of bacteria, chlamydiae, and viruses. The cultivation of Afipia spp. in the late 1980s appeared to answer the mystery of the identity of the agent. However, even more recent analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 86 publications
0
22
0
1
Order By: Relevance
“…The association between cats and the disease was first made by Debr'e in 1931. 1 Only in 1992 was Bartonella henselae (previously known as Rochalimaea henselae) shown to be the main causative agent. 2 Parinaud's oculoglandular syndrome is the most common ocular finding of CSD primary complex, appearing in 2-3% of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…The association between cats and the disease was first made by Debr'e in 1931. 1 Only in 1992 was Bartonella henselae (previously known as Rochalimaea henselae) shown to be the main causative agent. 2 Parinaud's oculoglandular syndrome is the most common ocular finding of CSD primary complex, appearing in 2-3% of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Brenner et al (1991) described the genus Afipia and two other species (Afipia clevelandensis and Afipia broomeae) and recognized three unnamed genospecies (1, 2 and 3). Apart from the report by English et al (1988), very little direct microbiological evidence linking A. felis and CSD has been presented and it is now clear that nearly all cases of CSD are due to a different bacterium, Bartonella henselae (Jerris & Regnery, 1996). Birkness et al (1992) demonstrated that A. felis has the capacity to grow intracellularly and have proposed a tissue culture protocol to isolate this species.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for wound-associated infections such as those caused by Bartonella henselae. B. henselae, an opportunistic and emerging pathogen, is carried by cats and causes several distinct clinical syndromes in immunocompetent individuals and AIDS patients including cat scratch disease, bacillary angiomatosis, chronic bacteremia, and valvular endocarditis (2,10,24,31,37,40). While several lines of evidence indicate a role for Fn in endovascular bacterial adherence during endocardial infections (21,30,42), other results strongly point to multifactorial events of bacterial adherence as the cause of heart valve damage (17).…”
mentioning
confidence: 99%